PRAYERS OF JESUS IN THE GOSPEL OF JOHN AS PARADIGMS - Edanad, Antony (Journal of Dharma, 2003)
In traditional Christian understanding prayer is seen as “speaking to God” or as “raising of the soul to God.” In fact, prayer is at the same time both conversation with God and conscious elevation of one’s whole being to God. There cannot be any conversation with God without the awareness of God’s ineffable reality and presence, and there cannot be any raising of one’s whole self to God without some kind of communication with God, verbal or non-verbal. Moreover, speaking to God involves listening to God and paying attention to his presence. Prayer has also a necessary communal dimension. Even in the case of personal prayer the praying individual stands in communion and solidarity with others. Prayer is and should be rooted in faith in God as one who is concerned about the humans and who makes himself accessible to them relating himself to them and intervening in their favour. The prayers of the Israelites found in the Bible are characterised by the recollection of the past deeds of God in their favour, certainty about his power and intention to intervene at present, and confidence and trust that he will accomplish his plan in the future.